Pengembangan Sistem Monitoring Penggunaan Air HIPPAM (Himpunan Penduduk Pemakai Air Minum) Dharma Tirta Desa Bogorejo Kecamatan Bancar-Tuban - Siti Julaikah; Bayu Priyambadha; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
HIPPAM Dharma Tirta Bogorejo Village is one of the Water Distribution Business Entities in Bogorejo Village, Bancar-Tuban District. The village head of Bogorejo explained that the management of HIPPAM's annual recapitulation and customer data is still done manually, which is recorded in a book. Customers also often do not pay attention to the amount of usage, do not remember the payment due and the absence of prior notice of problems related to HIPPAM. The clerk also still records the amount of usage and the amount of the customer's water payment by recording it in a book. This research will discuss the maximum data collection method for monitoring the amount of water use by making a website and android based application. The officer scans the QR Code as the customer id attached to each stand meter to enter customer data and will automatically be stored in the database. Notifications regarding HIPPAM issues are sent via SMS Gateway. The prototyping method is used because it has a development flow to find out the immediate needs of users and meet changing needs. Observations and interviews are used in the data collection process. Tests carried out namely testing functionality including unit testing and validation obtained all valid results. Non-functional testing is usability with the System Usability Scale (SUS) method. Based on the results of usability testing conducted, a score of 100 was obtained from the admin side, 82.5 from the customer side and 100 from the officer side. These figures prove and can be concluded if the application is acceptable, has good usability, convenience and satisfaction for the user.